Synthesizing and Studying the Structure of Ni(II) Complexes Containing 2-alkyliminomethyl Pyrene Ligands - Xuan Dien, Luong; Xuan Truong, Nguyen; Duc Quan, Ngo; Yamashita, Ken-ichi; Sugiura, Kenichi (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4809, 2018)
A bstract : The 1(Ni) and Ni(II) complex was synthesized based on the reaction between N,O-bidentate ligand 2-((methylimino)methyl) pyrene-1-ol (1) and nickel acetate in a mixed solvent of toluene, ethanol and NaOAc. The characters of the complex, such as elemental analysis (EA), IR, NMR, MS spectroscopy and single crystal X-ray diffraction, were investigated. With respect to the nickel atom, 1(Ni) complex adopts a distorted square planar trans -coordination geometry. Concerning the ligand arrangement, 1(Ni) complex has a step configuration with an angle of 35.5 o between the mean planes of the pyrene rings in the two independent molecules and step distance S = 1.93 Å, whereas the referent nickel(II) bis(salicylaldiminato) takes a much smaller step configuration with an angle of 17.6 o and step distance S = 0.845 Å (Chart 1).  Keywords: Coordination chemistry, Nickel, Pyrene, expanded ligand, salicylaldimine. References [1] H. Makio, T. Fujita, Acc. Chem. Res. 42 (2009) 1532. [2] H. Makio, N. Kashiwa, T. Fujita, Adv. Synth. Catal. 344 (2002) 477. [3] V. C. Gibson, S. K. Spitzmesser, Chem. Rev. 103 (2003) 283. [4] T. Matsugi, T. Fujita, Chem. Soc. Rev. 37 (2008) 1264. [5] D. A. Bansleben, S. K. Freiedrich, T. R. Younkin, R. H. Grubbs, C. Wnag, R.T. Li (1998) WO98/03165. [6] C. Wang, S. Friedrich, T. R. Younkin, R. T. Li, R. H. Grubbs, D. A. Bansleben, M. W. Day, Organometallics 17 (1998) 3149. [7] T. R. Younkin, E. F. Connor, J. I. Henderson, S. K. Friedrich, R. H. Grubbs, D. A. Bansleben, Science, 287 (2000) 460. [8] E. F. Connor, T. R. Younkin, J. I. Henderson, A. W. Waltman, R. H. Grubbs, Chem. Commun. (2003) 2272. [9] W. H. Sun, H. Yang, Z. Li, Y. Li, Organometallics 22 (2003) 3678. [10] C. Carlini, A. Macinai, F. Masi, A. M. R. Galletti, R. Santi, G. Sbrana, A. Sommazzi, J. Polym. Sci. A 42 (2004) 2534. [11] C. Carlini, M. Martinelli, A. M. R. Galletti, G. Sbrana, J. Polym. Sci. A 44 (2006) 1514. [12] Q. Chen, J. Yu, J. Huang, Organometallics 26 (2007) 617. [13] M. Delferro, J. P. McInnis, T. J. Marks, Organometallics 29 (2010) 5040. [14] D. J. Darensbourg, C. G. Ortiz, J. C. Yarbrough, Inorg. Chem. 42 (2003) 6915. [15] H. Liang, J. Liu, X. Li, Y. Li, Polyhedron, 23 (2004) 1619. [16] Y. Chen, S. Mandal, A. Sen, Organometallics 29 (2010) 3160. [17] M. Kang, A. Sen, Organometallics 24 (2005) 3508. [18] L. F. Groux, T. Weiss, D. N. Reddy, P. A. Chase, W. E. Piers, T. Ziegler, M. Parvez, J. Benet-Buchholz, J. Am. Chem. Soc. 127 (2005) 1854. [19] T. Hu, Y.G. Li, Y.S. Li, N. H Hu, J. Mol. Catal. A: Chem. 253 (2006) 155. [20] K. Ishizaki, S. Washimi, K. Kimura, (1999) JP200172654. [21] J. C. Jenkins, M. Brookhart, J. Am. Chem. Soc. 126 (2004) 5827. [22] F. Y. Pong, S. Mandal, A. Sen, Organometallics 33 (2014) 7044. [23] Y. Murata, H. Ohgi, T. Fujihara, J. Terao, Y. Tsuji, Inorg. Chim. Acta 368 (2011) 237. [24] T. Wiedemann, G. Voit, A. Tchernook, P. Roesle, I. Goettker-Schnetmann, S. Mecking, J. Am. Chem. Soc. 136 (2014) 2078. [25] A. Osichow, C. Rabe, K. Vogtt, T. Narayanan, L. Harnau, M. Drechsler, M. Ballauff, S. Mecking, J. Am. Chem. Soc. 135 (2013) 11645. [26] P. Wehrmann, S. Mecking, Organometallics 27 (2008) 1399. [27] I. Göttker-Schnetmann, P. Wehrmann, C. Roehr, S. Mecking, Organometallics 26 (2007) 2348. [28] I. Göttker-Schnetmann, B. Korthals, S. Mecking, J. Am. Chem. Soc. 128 (2006) 7708. [29] P. Wehrmann, M. Zuideveld, R. Thomann, S. Mecking, Macromolecules 39 (2006) 5995. [30] F. M. Bauers, S. Mecking, Macromolecules 34 (2001) 1165. [31] K. Iwase, H. Houjou, Y. Yamamura, K. Saito, Chem. Lett. 42 (2013) 1040. [32] K. Iwase, Y. Nagano, I. Yoshikawa, H. Houjou, Y. Yamamura, K. Saito, J. Phys. Chem. C 42 (2013) 1040. [33] L. X. Dien, K. Yamashita, M. S. Asano, K. Sugiura, Inorg. Chim. Acta 432 (2015) 103. [34] L. X. Dien, K. Yamashita, K. Sugiura, Polyhedron 102 (2015) 69-74. [35] L. Sacconi, M. Ciampolini, J. Chem. Soc. (1964) 276. [36] Y. Mei, W. Wang, S. Zhang, Z. Kristallogr. NCS 226 (2011) 539. [37] L. Sacconi, M. Ciampolini, J. Am. Chem. Soc. 85 (1963) 1750. [38] L. Sacconi, J. Chem. Soc. (1963) 4608. [39] A. Chakravorty, R. H. Holm, Inorg. Chem. (1964) 3(7). [40] S. Hara, H. Houjou, I. Yoshikawa, K. Araki, Cryst. Growth Des. 11 (2011) 5113.